The Collagenase of the Bacterium Clostridium histolyticum in the Treatment of Irradiation-Induced Capsular Contracture - Diehm, Yannick F; Hirche, Christoph; Berger, Martin R; Heil, Jörg; Golatta, Michael; Kotsougiani, Dimitra; Pomahač, Bohdan; Kneser, Ulrich; Fischer, Sebastian (Aesthetic plastic surgery, 2019)
BACKGROUND: Irradiation therapy is an important pillar in the treatment of breast cancer. However, it can trigger capsular fibrosis, the most significant complication of implant-based breast reconstruction. As collagen is the main component of fibrotic capsules, the collagenase of the bacterium Clostridium histolyticum poses a potential treatment option for this pathological condition. METHODS: Thirty-six rats received miniature silicone implants on their backs. On day 1, the implant sites of two groups were irradiated with 10 Gy. On day 120, one irradiated group received collagenase injections into the implant pockets (n = 12). Non-irradiated (n = 12) and irradiated capsules (n = 12) were injected with plain solvent solution serving as controls. Data were analyzed by means of in vivo imaging, histology, immunohistochemistry and gene expression analysis. RESULTS: Compared with both controls, the injection of collagenase led to significantly thinner capsules. This was verified by in vivo imaging and histology. Although irradiation provoked alterations in capsule collagen structure and vessel wall thickness, the application of collagenase resulted in a significant reduction of collagen density. This was accompanied by an up-regulation of VEGF-A gene expression. Of note, hematoma formation inside the implant pocket occurred in two cases after collagenase injection. CONCLUSIONS: The collagenase of the bacterium Clostridium histolyticum is effective in degrading irradiation-induced capsular fibrosis around silicone implants. Hematoma formation occurred most likely because of irradiation-induced alterations in vessel wall architecture and capsule vascularization. Further studies need to be performed to address the clinical safety of this novel treatment option.
Keywords: Implant Capsular Contracture; krysa rodu Rattus; Animals; Collagenases; potkani inbrední LEW; Clostridium histolyticum; prsní implantáty; Radiation Injuries; Rats; Female; zvířata; Breast Implants; radiační poranění; kolagenasy; Rats, Inbred Lew; kapsulární kontraktura; ženské pohlaví